2018
DOI: 10.1371/journal.pmed.1002654
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes genetic loci informed by multi-trait associations point to disease mechanisms and subtypes: A soft clustering analysis

Abstract: BackgroundType 2 diabetes (T2D) is a heterogeneous disease for which (1) disease-causing pathways are incompletely understood and (2) subclassification may improve patient management. Unlike other biomarkers, germline genetic markers do not change with disease progression or treatment. In this paper, we test whether a germline genetic approach informed by physiology can be used to deconstruct T2D heterogeneity. First, we aimed to categorize genetic loci into groups representing likely disease mechanistic pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
489
2
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 439 publications
(531 citation statements)
references
References 74 publications
28
489
2
12
Order By: Relevance
“…To gauge if these transcribed elements could be relevant for diverse disease/traits, we computed enrichment for islet TCs to overlap GWAS loci for 116 traits from the NHGRI catalog (Buniello et al 2019) and other relevant studies (Udler et al 2018). We observed that traits such as Fasting Glucose (FGlu) (fold enrichment = 7.05, P value = 3.30x10 -4 ), metabolic traits (fold enrichment = 6.46, P value = 2.03x10 -4 ) were among the most highly enriched, highlighting the relevance of these transcribed elements for islet biology ( Figure. 1F, Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gauge if these transcribed elements could be relevant for diverse disease/traits, we computed enrichment for islet TCs to overlap GWAS loci for 116 traits from the NHGRI catalog (Buniello et al 2019) and other relevant studies (Udler et al 2018). We observed that traits such as Fasting Glucose (FGlu) (fold enrichment = 7.05, P value = 3.30x10 -4 ), metabolic traits (fold enrichment = 6.46, P value = 2.03x10 -4 ) were among the most highly enriched, highlighting the relevance of these transcribed elements for islet biology ( Figure. 1F, Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Because T2D is orchestrated through a complex interplay between islet beta cell dysfunction and insulin resistance in peripheral tissues, we reasoned that some underlying pathways in T2D might be more relevant in islets than others. To explore this rationale, we utilized results from a previous study that analyzed GWAS data for T2D along with 47 other diabetes related traits and identified clusters of T2D GWAS signals (Udler et al 2018). Interestingly, we observe that GWAS loci in the islet beta cell and proinsulin cluster were highly enriched to overlap islet TCs (fold enrichment = 5.62, P value = 0.004), whereas loci in the insulin resistance cluster were depleted (fold enrichment = 0.97; Figure 1F, Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the top and bottom 2.5% of the distribution differ in risk of diabetes by ~ 10‐fold. These 400 variants can be grouped together according to the pathophysiological process they affect into what have been termed process‐specific polygenic risk scores, e.g., those affecting beta‐cell function, or fat distribution . These have modest effects on the underlying trait, and as diabetes drugs act on these particular traits, one would hope that these process‐specific polygenic risk scores will have moderate impact on glycemic response to diabetes drugs.…”
Section: Future Studies Of Pharmacogenetics In Diabetesmentioning
confidence: 99%
“…Often defined according to arbitrary diagnostic criteria, complex 65 diseases can represent the phenotypic convergence of numerous genetic etiologies (4)(5)(6)(7)(8). 66Recent studies in type 2 diabetes support the concept that there are disease subtypes with 67 distinct genetic architecture (7,8). Identifying and addressing genetic heterogeneity in 68 complex diseases could increase power to detect causal variants and improve treatment 69 efficacy (9).…”
mentioning
confidence: 99%
“…Understanding the genetic architecture of complex diseases is a central challenge in 64 human genetics (1-3). Often defined according to arbitrary diagnostic criteria, complex 65 diseases can represent the phenotypic convergence of numerous genetic etiologies (4)(5)(6)(7)(8). 66…”
mentioning
confidence: 99%